Pokémon adventures. 04 - Kusaka, Hidenori (VIZ Media, LLC, 2020)
"All your favorite Pokemon game characters jump out of the screen into the pages of this action-packed manga! A stylish new omnibus edition of the best-selling Pokemon Adventures manga series, collecting all the original volumes of the series you know and love. The three Legendary Pokemon Suicune, Raikou and Entei are searching for worthy Trainers. Will each be able to find someone powerful enough to fight by their side? Meanwhile, Crystal and Yellow have teamed up to find a mysterious flying Pokemon."--Provided by publisher.